Evaluation of the Electronic Traffic Law Enforcement Program on Traffic Violations: A Case Study at the Semarang City Police Department - Atmojo, Setiaji Nor; Kusumastuti, Retno (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
As the times evolve, technology and information become more modern in the digital era. Along with that, the demands and expectations of the community for the performance of the Indonesian National Police (Polri) in providing protection, supervision, and services will increase. The innovation of services by adopting information technology has also been carried out by Polri, with one of the efforts being the enhancement of electronic-based services. Polri has developed an electronic ticketing system known as Electronic Traffic Law Enforcement (ETLE). The ETLE program digitizes the ticketing process through the collaboration of technologies such as closed-circuit television (CCTV) combined with automatic number plate recognition (ANPR) technology. This enables the capturing of traffic violations and the identification of the offenders through their vehicle license plates. It is hoped that by implementing this electronic system, the entire ticketing process will become more efficient and free from illegal fees collected by law enforcement officers. Starting from March 23, 2021, the Semarang City Police Department (Polrestabes Semarang) has implemented the ETLE program in Semarang City to electronically enforce traffic violations. This is done to improve driving discipline and traffic order within the community, aiming to prevent traffic law violations and accidents. However, in its implementation, the ETLE program in Semarang City has not yet maximally influenced the public in adhering to traffic regulations. This is due to various challenges that have occurred in the field, necessitating the need for improvement or evaluation of the ETLE program to make its implementation more effective.